Kolaborasi Komunitas dalam Mendukung Ibu Berduka: Intervensi Psikologis bagi Keluarga dengan Anak Berpenyakit Langka - Ziadatul Hikmiah; Ade Meutia; Siti Sara Deviana; Dewi Sri Mustikasari (Universitas Teuku Umar, 2025)
Losing a child to a rare disease is a very traumatic experience for parents, especially mothers. This community service program, titled “Grief Support for Mothers Who Have Lost Children to Rare Diseases,” aims to provide psychological support for mothers who are grieving. Held virtually from May to June 2024 in collaboration with Enabled.id, this program is a psychological intervention structured based on the 5 stages of PATH (problem, analysis, test, and help) which results in a series of intervention programs consisting of education about the stages of grief, sharing in groups, and mindfulness techniques to help emotional recovery, followed by journaling sessions, and identification of grief triggers. The sessions were conducted in five groups of 15 mothers who had lost their children to rare diseases/disabilities, recruited through the Enabled.id network. Undergraduate psychology students also participated as assistants, gaining practical experience through internships at Enabled.id. The program achieved 100% of its goals, receiving positive feedback from participants who felt validated and equipped with tools to manage grief. This program demonstrates the positive benefits of a group-based grief intervention in improving psychological well-being and highlights the importance of collaborative community engagement efforts as a support system. Future development directions should be to expand the reach of the program to more families in need.